2017
DOI: 10.1007/s12630-017-0815-2
|View full text |Cite
|
Sign up to set email alerts
|

Muscular body build and male sex are independently associated with malignant hyperthermia susceptibility

Abstract: Muscular body build and male sex are strongly associated with MHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…While many children experienced life-threatening responses to heat, adults with similar RYR1 mutations generally experienced only muscle cramps or exercise intolerance (Supplementary Datas 1 and 2 ). Similar to previously reported findings for anesthetic-induced MH cases 41 , 42 , the proportion of heat-sensitive patients observed in male carriers of RYR1 variants was significantly higher compared to that of the female carriers (Fig. 1b, c ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…While many children experienced life-threatening responses to heat, adults with similar RYR1 mutations generally experienced only muscle cramps or exercise intolerance (Supplementary Datas 1 and 2 ). Similar to previously reported findings for anesthetic-induced MH cases 41 , 42 , the proportion of heat-sensitive patients observed in male carriers of RYR1 variants was significantly higher compared to that of the female carriers (Fig. 1b, c ).…”
Section: Resultssupporting
confidence: 91%
“…We conducted a retrospective cohort study and a systematic review to provide an up-to-date, comprehensive summary of the documented cases. As anticipated from previous reports 7,41,89 , we found that young age and male gender are significant risk factors for heat-sensitivity among individuals with RYR1 variants associated with MHS. Children with MHS, especially infants, are the most vulnerable to heat-induced death.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…37 Recently, male sex and body build subjectively assessed as muscular have been reported as independent predictors of MH susceptibility. 39 However, whether a larger muscle mass is associated with MH sex discrepancy warrants objective assessment. On the whole, the pathomechanism leading to sex differences in the penetrance of MH is still unknown, but epigenetic RYR1 allele silencing has been ruled out as a cause of reduced penetrance of MH susceptibility in females.…”
Section: Penetrance Of Malignant Hyperthermiamentioning
confidence: 99%
“…[5][6][7] The awake episodes are rare, and present with non-specific symptoms ranging from hyperthermia, muscle cramps, exertional pain, and rhabdomyolysis to a lifethreatening hypermetabolic reaction in physically fit and seemingly healthy individuals often without a personal or family history of MH, which makes the diagnosis challenging. [7][8][9][10] We report two fatal cases of awake MH episodes in one extended family with a strong history of anesthetic-induced MH episodes and deaths demonstrating the close connection between anesthesia-induced MH and awake MH episodes. This report is intended to raise awareness among patients and medical personnel (anesthesiologists, emergency department [ED], intensive care physicians, and nurses) to the possibility of life-threatening MH episodes that may develop in MHS individuals in the absence of general anesthesia.…”
mentioning
confidence: 98%